Effect of comprehensive cancer genomic profiling on therapeutic strategies and clinical outcomes in patients with advanced biliary tract cancer: A prospective multicenter study - Takada, Kohichi; Kubo, Tomohiro; Kikuchi, Junko; Yoshida, Makoto; Murota, Ayako; Arihara, Yohei; Nakamura, Hajime; Nagashima, Hiroyuki; Tanabe, Hiroki; Sugita, Shintaro; Tanaka, Yumi; Miura, Ayana; et al. (Frontiers in Oncology, 2022)
Characterization of the genomic landscape of biliary tract cancer (BTC) may lead to applying genotype-matched therapy for patients with this disease. Evidence that comprehensive cancer genomic profiling (CGP) guides genotype-matched therapy to improve clinical outcomes is building. However, the significance of CGP in patients with BTC remains unclarified in clinical practice. Therefore, the purposes of this study were to assess the utility of CGP and identify associations between clinical outcomes and genomic alterations in patients with BTC. In this prospective analysis, detection rates for actionable genomic alterations and access rates for genotype-matched therapy were analyzed in 72 patients with advanced BTC who had undergone commercial CGP. Cox regression analyses assessed relationships between overall survival and genomic alterations detected with CGP. The most common genomic alterations detected were TP53 (41, 56.9%), followed by CDKN2A/B (24, 33.3%/20, 27.8%), and KRAS (20, 27.8%). Actionable genomic alterations were identified in 58.3% (42/72) of patients. Detection rates for FGFR2 fusions, IDH1 mutations, and BRAF V600E were low in this cohort. Eight (11.1%) patients received genotype-matched therapy. For patients with intrahepatic cholangiocarcinoma (ICC), CDKN2A/B loss was associated with shorter overall survival. These real-world data demonstrate that CGP can identify therapeutic options in patients with advanced BTC. CDKN2A/B loss was identified as a poor prognostic factor in patients with ICC. Thus, this study provides a rationale for considering CGP in planning therapeutic strategies for advanced BTC.